2023
DOI: 10.3390/genes14030705
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Diversity of SARS-CoV-2 in Ethiopia, 2020–2022

Abstract: Ethiopia is the second most populous country in Africa and the sixth most affected by COVID-19 on the continent. Despite having experienced five infection waves, >499,000 cases, and ~7500 COVID-19-related deaths as of January 2023, there is still no detailed genomic epidemiological report on the introduction and spread of SARS-CoV-2 in Ethiopia. In this study, we reconstructed and elucidated the COVID-19 epidemic dynamics. Specifically, we investigated the introduction, local transmission, ongoing evolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…SN9 ). In relation with the Ethiopian variant survey of Sisay et al our key findings are confirmed 9 : The importance of B.1.480 (wildtype* in our case) and non-concerning B.1 sublinages (wildtype in our case), the minor role of beta and the general timeframe and dominance of alpha, delta, and omicron waves are common discoveries. Since the observation period of Sisay et al ends in February 2022, which is around the time when the statistical power of our sequencing data decreases substantially, future research about the precise transition between the omicron waves BA.1 and BA.4/5 could be worth exploring.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…SN9 ). In relation with the Ethiopian variant survey of Sisay et al our key findings are confirmed 9 : The importance of B.1.480 (wildtype* in our case) and non-concerning B.1 sublinages (wildtype in our case), the minor role of beta and the general timeframe and dominance of alpha, delta, and omicron waves are common discoveries. Since the observation period of Sisay et al ends in February 2022, which is around the time when the statistical power of our sequencing data decreases substantially, future research about the precise transition between the omicron waves BA.1 and BA.4/5 could be worth exploring.…”
Section: Discussionsupporting
confidence: 83%
“…The antibody data provide information about previous infections, but not about the SARS-CoV-2 variants which caused them. Moreover, up until very recently, there was no available data on virus variants in Ethiopia 9 . Hence, to better understand the pandemic, we sequenced a total of 1873 SARS-CoV-2 reverse transcription polymerase chain reaction (RT-PCR) positive swabs, collected in Jimma and Addis Ababa, between October 2020 and July 2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with our HRM assay, we could identify the infecting variant in many of these samples and describe the variant waves in Kisumu during this time. Our assay has shown three variant replacement events between February 2021 and January 2022, which mirrors the three waves reported during this period from other African countries such as The Gambia (21), Ethiopia (22), and Senegal (23). In the samples analysed from Kenya this study, Alpha was the dominant variant between March 2021-May 2021 and was then replaced by Delta in May 2021, followed by Omicron in mid-December 2021, which is in keeping with epidemiological data from other regions of Kenya (24,25).…”
Section: Discussionsupporting
confidence: 80%
“…The World Health Organization's (WHO) call for widespread genomic sequencing to strengthen disease surveillance highlights its critical role in global health [7,8]. However, there is a stark contrast in the sequencing capacity between high-income countries (HICs), which report more sequences per capita, and low-and middle-income countries (LMICs), despite the commendable efforts in some African nations [9][10][11]. Moreover, the urgent demand for genomic sequencing in public health from the pandemic has exposed several challenges in all economic contexts.…”
Section: Introductionmentioning
confidence: 99%